Assessment of FEAST (Feed Assessment Tool): Analysis on how it affects user Knowledge, attitudes, practices and subsequent livestock feeding strategies - Kiruja, Grace (University of Edinburgh, 2023)
The Feed Assessment Tool (FEAST) is a research for action tool that asses the availability and utilisation of local feed resources with the aim of creating context specific feed interventions. It is a tool that is more inclined towards pushing for participatory methods in agricultural research for development, while incorporating the increased use of technology in the developing world. With the increased introduction of technologies both in the form of interventions and technological tools that assist in the creation and implementation of interventions, it is important to carry out post-assessments to analyse the impact that these technologies have. This allows room for further improvement in existing interventions and the creation of better interventions in future. To understand the impact of FEAST, this study takes a qualitative approach rather than the conventional economic and market led assessments, to analyse the perception that FEAST users have on the impact of the tool on their level of knowledge, attitude and consequential livestock feeding strategies. By analysing the perception of FEAST users, we aim to get the actual opinion of the users of the tool and what they see happening in the contexts that they work in. The study results indicate a symbiotic relationship between the use of the tool and a push for participatory methods. Participants indicated a step-by-step process on how the use of the tool pushed for increased dialogue with livestock keepers which increased their level of knowledge on the contexts they were coming into. Consequentially, an increase in knowledge and improved feed systems understanding shifted their attitudes towards how they roll out feed interventions and generate data that influences implementing bodies. This study also analysed the impacts of FEAST on the livestock keepers based on the perception of the participants. From their perspective, a platform for livestock keepers to air their feed challenges and choose suitable interventions resulted in better uptake of said interventions and increased likelihood of their success. Although limited to facilitators of FEAST, this study did indicate a shift in the knowledge, attitude and the way feed interventions were rolled out after using FEAST. In future, it would be beneficial to carry out a broader analysis of 6 this study to directly analyse the perception of livestock keepers and other stakeholders on their perception of the impact of FEAST.